Integrating single-cell omics and materials science for uveal melanoma: from mechanistic insights to precision therapeutics - Fu, Shouyong; Li, Changfei (Frontiers in Oncology, 2025)
Uveal melanoma (UM), the most common primary intraocular malignancy in adults, presents significant clinical challenges due to its high metastatic potential, pronounced hepatic tropism, and poor prognosis upon systemic dissemination. Despite established local therapies, nearly half of patients develop distant metastases, highlighting an urgent need for more effective systemic strategies. Recent advances in single-cell omics technologies (e.g., scRNA-seq, scATAC-seq, spatial transcriptomics) have revolutionized our understanding of UM pathobiology. These approaches have meticulously delineated the complex tumor heterogeneity, immunosuppressive microenvironment, and key molecular drivers—including novel macrophage subsets (e.g., immunosuppressive MΦ-C4), senescent endothelial cells, and non-canonical immune checkpoint expression—providing unprecedented resolution for identifying actionable therapeutic targets. Concurrently, innovations in materials science and biomedical engineering offer transformative opportunities for precision therapy. Engineered nanocarriers, biodegradable implants, and advanced gene therapy vectors (e.g., tropism-enhanced AAVs, CRISPR-Cas9 systems) enabled targeted drug delivery, sustained release, and genetic modulation tailored to the eye’s unique anatomy and immune privilege. This review synthesizes these converging frontiers, outlining how the integration of multi-omics insights with smart biomaterials can overcome current therapeutic limitations. We catalog emerging material-based platforms applicable to UM and summarize validated molecular targets (e.g., GNAQ/GNA11, YAP/TAZ, BAP1, c-Met, CXCR4). Furthermore, we propose an interdisciplinary paradigm spanning combinatorial targeted therapies, immunomodulation, minimally invasive devices (e.g., robotic radiosurgery), and engineered delivery systems. By bridging mechanistic discovery with translational engineering, this synergy holds significant promise for advancing precision medicine and improving clinical outcomes in UM, ultimately facilitating the transition from bench to bedside.